“Aqui é uma casa masculina!” : juventude “trans” e socioeducação - Fontoura, Márjori Heitich (2019)
This research intends to give viability to an issue hardly discussed, both in the academic world and public policies. It is an experience lived in one of the units of compliance of socio-educational measure of the Fundação de Atendimento Socioeducativo do Rio Grande Sul (FASE RS), where the author of this research acts as a psychologist. The idea came up from the entering of a transgender teenager on an unit exclusively for young cisgender man between 12 and 21 years old. In the intention of legitimate his identity and trying to reach the best way of staying in that place, marked by male signs, the team attempted focused of the search for technical, literary and law guides, having as result the palpable misorientation. From this gap, the searcher, through this research, decided to contribute in the construction of theoretical and practical guides to support the development of an important guideline that is concretizing nowadays in society, materializing through the social militancy of LGBT rights for the rights of living and being part of society. Through this problematic found in the unit, considering the pedagogical proposal inherent to the educational measures guaranteed by the Child and Adolescent Statute (1990) and the approach to human rights, it is essential to think about the socio-education focused on the guarantees of integral protection of the LGBT youth, also (Lesbians, Gays, Bisexuals Transsexuals and Transgenders). To start the discussion of this work, beyond the lived experience, it was sought to perform a bibliographic review on the theme 'LGBT population in conflict with law', focusing on the socio-educational measure of hospitalization. The preference for the restricted environment happened because it is understood that it is in this place that the crossings occur in a more forceful way,with the conclusion that the issues of gender and sexuality end up being worsened by confinement. As the main scenario, the story of Rosa was presented, through the methodology of the case study, and her socio-educational trajectory with the team and other young people in compliance with socio-educational measure in the FASE. Thus, the work presented resulted from the joint experience between professionals, adolescents and young adults. The mishaps, solutions and crossings were reported, interweaving, also, interviews with professionals and young people who have worked (or not) in the search for solutions for an effective guarantee of rights on the period in which Rosa was deprived of her liberty. The difficulty of finding theoretical contributions and experiences on the topic points to the lack of public policies aimed at LGBT youth, because, as can be seen in other institutions, it does not find an adequate place even when "needs to be withdrawn" from society. Thus, the initial hypothesis was that socio-educational measures, highlighting the deprivation of liberty, do not present a program aimed at guaranteeing the integral protection of this population, in particular with a view to safeguarding the right to non-discrimination with regard to their gender identity and, consequently, the realization of rights relating to life, liberty, dignity, respect, the right to family and community coexistence, among others.